Comparison the level of Standard Deviation of N-N interval (SDNN) among Adolescent in Non Smokers and Smokers in Yogyakarta - Nurfazrin H. Akuba; Nurvita Risdiana (Faculty of Medicine, Universitas Islam Indonesia, 2018)
Background: Smoking has a negative impact on health. It makes an imbalance of the autonomic nervous system (ANS). It influenced the standard deviation of N-N interval (SDNN). SDNN has a duty as indicator for ANS controlled, consequently, SDNN in smokers is lower than non smokers because of ANS imbalance. Therefore, smokers have high risk for non communicable disease (NCD) in the future.Objective: This research’s purpose was to know the comparison of SDNN level among smokers and non smokers adolescent.Methods: This research was non-experimental study with descriptive comparative design and cross sectional approach. The samples divided into 2 groups with each of group consists of 20 students. They were chose by purposive sampling techniques. SDNN level was measured by electrocardiogram (ECG) for 5 minutes with the provision that they should no tea, caffeine, alcohol consumption and no heavy exercise within 2 hours before data collected, feel free from desire to go to bathroom, feeling relax when data collection were performed. The data was analyzed by Mann Whithey test.Results: There was a significant difference of between smokers’ SDNN and non smokers’ with p= 0.038 (p<0.05). Smokers’ SDNN was lower than non smokers’.Conclussion: Smokers’ SDNN level was lower than non smokers’.